Documenting Learning Moments, Journeys, and Expeditions as Teachers’ Reflection: A Book Review of the Writing Teacher’s Guide to Pedagogical Documentation - ANAS, Ismail (Politeknik Negeri Ujung Pandang, 2024)
Education is a dynamic and collaborative process where students play a pivotal role in their own learning journey. They surpass their traditional role as mere recipients of knowledge and become active partners in the learning process, inspiring and enriching educators’ practices. However, despite the immense value that lies within the activities that unfold within classrooms, these experiences often go undocumented and unnoticed. The documentation of classroom activities yielded pedagogical evidence, which served as data informing teachers’ decision-making and instructional practices. Pedagogical documentation is a tool for formative assessment to identify the students’ learning needs (Buldu, 2010; Rintakorpi, 2016). These needs can be generated from capturing classroom learning activities as data or documents for learning analytics (Jones & McCoy, 2020). By emphasizing practical processes, protocols, and tools for effective documentation, Stockman equips educators with the essential framework to capture and analyze the full spectrum of learning experiences. It also provides teachers with the necessary guidance to enhance their documentation practices and promote authentic and evidence-based learning for their students. It goes beyond theory, offering real-world case studies and examples from experienced documentarians who have harnessed the power of documentation in their own teaching contexts. It offers an opportunity to reimagine teaching practices and create inclusive and vibrant learning environments. This book is organized in three parts: 1) a comprehensive description of documentation, 2) how to plan and organize a documentation project, and 3) what tools and resources to document the students’ learning.